Eco-pesantren development: The challenges and opportunities of ecological conservation - Kristiyanto Kristiyanto; Hadi Sukadi Alikodra (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
Implementing green, eco-friendly, and sustainable development is difficult, hence highly dependent on attainable economic profit, and tends to be exploited massively and destructively to attain the desired benefits. It leads to environmental degradation and, consequently, the diminishing of several natural resources. Therefore, an alternative approach involving effective and Islam-based conservation as well as land restoration is required. In this study, in-depth individual interviews on pesantren Al-Zaytun were conducted to collect the qualitative descriptive data, including biotic aspects, such as plant diversity and wastewater treatment in water management and conservation. The results showed the pesantren Al-Zaytun utilized Tectona grandis and Eichhornia crassipes to carry out land and water management as a sustainable approach to conservation as well as food, water, and energy security development. Therefore, it can become a role model for eco-pesantren development in the modern era, as well as the utilization and management of natural resources for ecological development.